COVID-19 Vaccination Rates and Factors Affecting Vaccine Hesitancy among Pregnant Women during the Pandemic Period in Turkey: A Single-Center Experience - Düriye Sila Karagöz Özen; Arzu Karagöz Kiraz; Ömer Faruk Yurt; Ilknur Zeynep Kiliç; Mehmet Derya Demirağ (Vaccines, 2022)
The new coronavirus disease (COVID-19), which was detected in the Wuhan region of China in 2019 and spread rapidly all over the world, was declared a pandemic by the WHO in 2020. Since then, despite widespread recommendations to prevent the spread of the disease and provide treatment for sick people, 6,573,968 people died all over the world, 101,203 of which in Turkey. According to the international adult vaccination guidelines, pregnant women have been recommended to get vaccinated against the new coronavirus disease, as well as influenza and tetanus, during pregnancy. Before this study, not enough information was available about the vaccination awareness and vaccination hesitancy rates of pregnant women living in Turkey. For this reason, we believe that our study will contribute to filling this gap in the literature. The main objective of this study was to investigate the vaccination rates of pregnant women in a local hospital in Turkey and the reasons for vaccine hesitancy in this patient group. The minimum sample size of the study was found to be 241, with 80% power, 0.2 effect size, and 95% confidence interval, at p < 0.05 significance level. We included 247 consecutive pregnant women who applied to the Samsun Training and Research Hospital Gynecology and Obstetrics Outpatient Clinics between January 2022 and April 2022. The researchers prepared a questionnaire by taking into account the characteristics of the local community. A preliminary survey with these questions was also conducted before starting the main study. The mean age of the pregnant women participating in the study was 28.7 ± 5.3 years, and the mean gestational age was 28.2 ± 7.9 weeks. Among the participants, 26.3% were university graduates or had a higher degree, and 17% were actively working; in addition, 93 (37.7%) of the 247 pregnant women had received the COVID-19 vaccine, 203 (82.2%) had received at least one dose of the tetanus vaccine, and only 1 (0.4%) person had been administered the influenza vaccine during pregnancy. The most common reason for COVID-19 vaccine refusal and hesitancy was safety concerns, while the low rates of tetanus and influenza vaccination were due to a lack of knowledge. These results show that it is important to inform and educate the pregnant population on this subject to improve their vaccination behavior.